Diatomaceous Earths – Natural Insecticides (Pesticides and Phytomedicine / Pesticidi i fitomedicina, 2013)
The regulatory issues for diatomaceous earth (DE) cover three fields: consumer safety, worker safety, and proof of efficacy against pests. For consumer safety, regulatory issues are similar to those for other additives, and a principal benefit of DEs is their removal by normal processing methods. For worker safety, regulatory issues are similar to those for other dusts, such as lime. The proof of potential insecticide values of DE may be assessed by using the analysis of physical and chemical properties of DE and its effect on grain properties and the proof of efficacy may be regulated by bioassay of standard design. Integrated pest management (IPM), a knowledge-based system, is rapidly providing a framework to reduce dependence on synthetic chemical pesticides. The main principle of post-harvest IPM is to prevent problems rather than to react to them. The specific curative measures using synthetic pesticides should be applied only when infestation occurs. DE and enhanced diatomaceous earth (EDE) formulations hold significant promise to increase the effectiveness and broaden the adoption of IPM strategies, thereby reducing the need for synthetic pesticides. By incorporating DE in an effective IPM program, grain is protected against infestation, loss caused by insects is prevented and grain quality is maintained until the grain is processed. Cases study data on the use of DE for commodity and structural treatment show that DE is already a practical alternative to synthetic pesticides in some applications.
Keywords: Stored products; Diatomaceous Earths; Safety; Insecticides